Maternal Role Attainment and Quality of Life of Primiparous Adolescent Mothers: A Qualitative Study : Maternal Role Attainment and Quality of Life of Primiparous Adolescent Mothers - Sariati, Yuseva (Jurnal Kesehatan - STIKes Prima Nusantara, 2025)
The purpose of this study is to understand the experiences of primiparous adolescent mothers in achieving maternal roles. Adolescent motherhood presents unique challenges due to the immaturity and societal pressures these young mothers face. A qualitative study was conducted using in-depth interviews with 12 primiparous adolescent mothers in Probolinggo, East Java, Indonesia. Participants were selected through purposive sampling, and data were analyzed using deductive-inductive thematic analysis with Nvivo 12 software. Five main categories emerged: reasons for early marriage, feelings of first-time mothers, challenges of being a mother, coping strategies, and maternal role attainment. Key findings include cultural and economic reasons for early marriage, mixed emotions of joy and fear among first-time mothers, challenges like emotional stress and social isolation, coping strategies involving support systems and self-care, and the process of maternal identity formation. The study highlights the complex interplay of cultural, economic, and emotional factors influencing adolescent motherhood. Effective interventions should consider these factors to support adolescent mothers in their transition to motherhood. Adolescent mothers face multifaceted challenges that require tailored support systems to help them navigate motherhood and improve their overall quality of life.